THE AIRLINE’S RELIABILITY PROGRAM - Тамаргазін, О. А.; Власенко, П. О. (Science-based technologies, 2013)
Airline’s operational structure for Reliability program implementation — engineering division, reliability division, reliability control division, aircraft maintenance division, quality assurance division — was considered. Airline’s Reliability program structure is shown. Using of Reliability program for reducing costs on aircraft maintenance is proposed.